Growth, Physiological, and Intestinal Responses of Low-Weight Day-Old Broiler Chicks to Dietary Infertile Egg Powder - Handayani, F. R.; Widiastuti, E.; Agusetyaningsih, I.; Yudiarti, T.; Sari, D. A. P.; Sugiharto (Faculty of Animal Science, IPB University, 2025)
The present study examined the consequences of supplementing the diets of low-weight day-old broiler chicks (DOC) with 4% infertile egg powder (IEP). The chicks were categorized into three groups namely; normal-weight DOC, low-weight DOC on a basal diet, and low-weight DOC on a diet that contained 4% IEP (T2). In hematological analysis, there was increase in hemoglobin levels, and mean corpuscular hemoglobin concentration (MCHC) compared to T2, but the MCV was less than T0 (p<0.05). There was improvement in the lipid metabolism, whereby triglyceride and HDL levels reduced and increased, respectively (p<0.05). T2 showed an improved antioxidant status; it had an increased activity of superoxide dismutase (SOD) and a decreased level of malondialdehyde (MDA) (p<0.05). Ileal lactic acid bacteria (LAB) and coliform counts were also substantially reduced in T2 vs. T0 (p<0.05), whereas both caecal coliform counts and LNE counts and the LAB-to-coliform ratio were significantly worse in T1 and T2 than T0 (p<0.05). Histological findings expressed the aspect of villus height-to-crypt depth (VH/CD) ratio that was greater in duodenum and ileum of T2 than T1, and deeper crypt in the jejunum in T0 than T1 (p<0.05). There was significant reduction in lesion score in duodenum and the jejunum as seen in T2 group (p<0.05). T2 also had much higher weight gain (p<0.05). per day, feed consumption and body weight at the end when compared to T1. To summarize the findings, the supplement of 4% IEP via the diet improved the physiological functioning and intestinal health status, causing the rise in body weights in low-weight broiler chicks.